Thromboelastography in COVID-19 patients: An observational study in the South African context - Bavinash Pillay; Sarah A. van Blydenstein; Shahed Omar (African Journal of Laboratory Medicine, 2025)
Background: Coronavirus disease 2019 (COVID-19) increases the risk of venous thromboembolism, requiring monitoring of low molecular weight heparin (LMWH) via a time-consuming, costly and often unavailable test – anti-factor Xa (anti-Xa). An affordable, rapid point-of-care alternative, the thromboelastogram, is available, but performance comparisons to anti-Xa are lacking.